Paradoxical Effect of Actinomycin D: Regulation of Synthesis of Wound RNase at Translation in Turnip Tissue - Sacher, Joseph A. (1975)
Cutting of tissue sections induces RNase (EC 2.7.7.16) activity (phase I) in white turnip (Brassica rapa L. var. rapa) which peaks in 4 or 7 hours and then declines rapidly (phase II). The increase is inhibited by cycloheximide; also RNase from tissue bathed in 99.8% D(2)O during phase I underwent a large increase in buoyant density, indicating that the increased activity is due to de novo synthesis. Actinomycin D inhibited induction of RNase only if given within the initial 45 minutes after cutting. When it was applied after 45 minutes, it caused enhancement (super-induction) of RNase activity for over 24 hours. The half-time for degradation of RNase during phase I in the presence of cycloheximide and phase II in the presence and absence of cycloheximide is the same, indicating that the decline in RNase activity is due to cessation of synthesis. Also the rate of degradation of RNase remains the same during superinduction, thus indicating that actinomycin D superinduction is due to maintenance of synthesis of RNase rather than inhibition of its rate of degradation. Consistent with this is the fact that actinomycin D superinduction of RNase is inhibited by cycloheximide. The evidence is consistent with the hypothesis that messenger RNA for RNase is long-lived and the decline in RNase is due to transscription of a regulator gene coding for a specific repressor protein during phase I which inhibits RNase synthesis at the level of translation. Superinduction of RNase activity by actinomycin D is explicable in terms of (a) inhibition of synthesis of the mRNA coding for a repressor protein that inhibits translation of RNase-specific mRNA, or, (b) differential stability of mRNAs in presence of actinomycin D, and competition among mRNAs for factors rate-limiting to translation, thus favoring synthesis of proteins coded by long-lived messengers.